Development of a Kit for Rapid Immunochromatographic Detection of Sacbrood Virus Infecting Apis cerana (AcSBV) Based on Polyclonal and Monoclonal Antibodies Raised against Recombinant VP1 and VP2 Expressed in Escherichia coli - Song Hee Lee; Tae-Kyun Oh; Sung Oh; Seongdae Kim; Han Byul Noh; Nagarajan Vinod; Ji Yoon Lee; Eun Sun Moon; Chang Won Choi (Viruses, 2021)
A Korean isolate of the sacbrood virus infecting Apis cerana (AcSBV-Kor) is the most destructive honeybee virus, causing serious economic damage losses in Korean apiculture. To address this, here, we attempted to develop an assay for the rapid detection of AcSBV-Kor based on immunochromatographic detection of constituent viral proteins. Genes encoding VP1 and VP2 proteins of AcSBV-Kor were cloned into an expression vector (pET-28a) and expressed in Escherichia coli BL21(DE3). During purification, recombinant VP1 (rVP1) and VP2 (rVP2) proteins were found in the insoluble fraction, with a molecular size of 26.7 and 24.9 kDa, respectively. BALB/c mice immunized with the purified rVP1 and rVP2 produced polyclonal antibodies (pAbs) such as pAb-rVP1 and pAb-rVP2. Western blot analysis showed that pAb-rVP1 strongly reacted with the homologous rVP1 but weakly reacted with heterologous rVP2. However, pAb-rVP2 strongly reacted not only with the homologous rVP2 but also with the heterologous rVP1. Spleen cells of the immunized mice fused with SP2/0-Ag14 myeloma cells produced monoclonal antibodies (mAbs) such as mAb-rVP1-1 and mAb-rVP2-13. Western blot analysis indicated that pAb-rVP1, pAb-rVP2, mAb-rVP1-1, and mAb-rVP2-13 reacted with AcSBV-infected honeybees and larvae as well as the corresponding recombinant proteins. These antibodies were then used in the development of a rapid immunochromatography (IC) strip assay kit with colloidal gold coupled to pAb-rVP1 and pAb-rVP2 at the conjugate pad and mAb-rVP1-1 and mAb-rVP2-13 at the test line. One antibody pair, pAb-rVP1/mAb-VP1-1, showed positive reactivity as low as 1.38 × 103 copies, while the other pair, pAb-rVP2/mAb-VP2-13, showed positive reactivity as low as 1.38 × 104 copies. Therefore, the antibody pair pAb-rVP1/mAb-VP1-1 was selected as a final candidate for validation. To validate the detection of AcSBV, the IC strip tests were conducted with 50 positive and 50 negative samples and compared with real-time PCR tests. The results confirm that the developed IC assay is a sufficiently sensitive and specific detection method for user-friendly and rapid detection of AcSBV.